Pulmonary Artery Pseudoaneurysm: A Rare Cause of Fatal Massive Hemoptysis - Himaja Koneru; Sreeja Biswas Roy; Monirul Islam; Hesham Abdelrazek; Debabrata Bandyopadhyay; Nikhil Madan; Pradnya D. Patil; Tanmay S. Panchabhai (Case Reports in Pulmonology)
Pulmonary artery pseudoaneurysm (PAPA), an uncommon complication of pyogenic bacterial and fungal infections and related septic emboli, is associated with high mortality. The pulmonary artery (PA) lacks an adventitial wall; therefore, repeated endovascular seeding of the PA with septic emboli creates saccular dilations that are more likely to rupture than systemic arterial aneurysms. The most common clinical presentation of PAPA is massive hemoptysis and resultant worsening hypoxemia. Computed tomography angiography is the preferred diagnostic modality for PAPA; typical imaging patterns include focal outpouchings of contrast adjacent to a branch of the PA following the same contrast density as the PA in all phases of the study. In mycotic PAPAs, multiple synchronous lesions are often seen in segmental and subsegmental PAs due to ongoing embolic phenomena. The recommended approach for a mycotic PAPA is prolonged antimicrobial therapy; for massive hemoptysis, endovascular treatment (e.g., coil embolization, stenting, or embolization of the feeding vessel) is preferred. PAPA resection and lobectomy are a last resort, generally reserved for patients with uncontrolled hemoptysis or pleural hemorrhage. We present a case of a 28-year-old woman with necrotizing pneumonia from intravenous drug use who ultimately died from massive hemoptysis and shock after a ruptured PAPA.